Del papel al sonido. La difusión del fondo musical del CRAI Biblioteca de Fondo Antiguo de la Universitat de Barcelona. - Brugarolas Bonet, Oriol; Verger Arce, Neus (My University, 2026)
La comunicación presenta la colección musical del CRAI Biblioteca de Fondo Antiguo de la Universidad de Barcelona. Después de exponer los criterios catalográficos para garantizar su acceso, se exponen las acciones llevadas a cabo para su difusión: colección editorial, jornadas de patrimonio musical, exposiciones, recuperación y grabación de piezas musicales, conciertos y página web. Todo ello ha creado una red de alianzas que van más allá del CRAI y de la Universidad de Barcelona y que tiene como objetivo dar a conocer este rico patrimonio musical desde distintas perspectivas.

This paper presents the music collection held at the University of Barcelona's Rare Book and Manuscript CRAI Library. After outlining the cataloguing criteria used to ensure its accessibility, the study details various initiatives undertaken to its dissemination: editorial collection, conferences on musical heritage, curated exhibitions, recovery and recording of musical works, concerts and web page. These efforts have fostered a network of partnerships extending beyond the University, all aimed at raising awareness of this rich musical heritage from diverse perspectives.
From paper to sound. The dissemination of the musical collection of the Rare Book and Manuscript CRAI Library of the University of Barcelona
Keywords: Patrimonio musical; Difusión y promoción (Marketing)